Can butyrate prevent colon cancer? The AusFAP study: A randomised, crossover clinical trial - Julie Clarke; Alex Boussioutas; Brooke Flanders; Trevor Lockett; Karen Harrap; Ian Saunders; Patrick Lynch; Mark Appleyard; Allan Spigelman; Don Cameron; Finlay Macrae (Contemporary Clinical Trials Communications, 2023)
Increased colonic butyrate from microbial fermentation of fibre may protect from colorectal cancer (CRC). Dietary butyrylated high amylose maize starch (HAMSB) delivers butyrate to the large bowel. The objective of this clinical trial (AusFAP) is to evaluate potential chemoprotective effects of HAMSB on polyposis in individuals with a genetic form of colon cancer, Familial Adenomatous Polyposis (FAP).The study is a multi-site, double blind, randomised, placebo-controlled crossover trial undertaken at major hospitals in Australia. After a baseline endoscopy participants consume either 40g/day of HAMSB or placebo (low amylose maize) starch for 26 weeks. After another endoscopic examination participants consume the alternate starch for 26 weeks. A third endoscopy at 52 weeks is followed by 26 weeks' washout and a final endoscopy at 78 weeks. Primary outcome measure is the global large bowel polyp number. Secondary measures include global polyp size counts, and number and size of polyps at two tattoo sites: one cleared of polyps at baseline, and another safely chosen with polyps left in situ during the study. Other secondary outcome measures include the effects of intervention on cellular proliferation in colonic biopsies, faecal measures including short chain fatty acid concentrations, and participants’ dietary intakes. Generalized linear mixed models analysis will be used to estimate differences in primary outcomes between intervention and placebo periods.This study represents the first clinical evaluation of the effects of increased colonic butyrate on polyp burden in FAP which, if effective, may translate to lower risk of sporadic CRC in the community.Australian New Zealand Clinical Trials Registry Number: 12612000804886.